2006
DOI: 10.1007/s11010-006-2494-0
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic interactions of Ferulic acid with Ascorbic acid: Its cardioprotective role during isoproterenol induced myocardial infarction in rats

Abstract: Studies on the lipid peroxidation and antioxidant changes and their significance during myocardial injury have provided a new insight into the pathogenesis of heart disease. The heart failure subsequent to myocardial infarction may be associated with an antioxidant deficit as well as increased myocardial oxidative stress. The present study was designed to evaluate the effect of the combination of ferulic acid and ascorbic acid on antioxidant defense system and lipid peroxidation against isoproterenol (ISO)-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 45 publications
4
43
0
Order By: Relevance
“…Many studies have reported that increased levels of AST, ALT, LDH, GGT, and CPK are consistently correlated with cardiac infarcts (Yogeeta et al, 2006;Rajadurai and Stanely, 2007). Myocardial cell damage induced by heat stress was observed through the gradual elevation of LDH, AST, and CK levels in the present study.…”
Section: Discussionsupporting
confidence: 66%
“…Many studies have reported that increased levels of AST, ALT, LDH, GGT, and CPK are consistently correlated with cardiac infarcts (Yogeeta et al, 2006;Rajadurai and Stanely, 2007). Myocardial cell damage induced by heat stress was observed through the gradual elevation of LDH, AST, and CK levels in the present study.…”
Section: Discussionsupporting
confidence: 66%
“…AST starts to rise about 12 hours after infarction and reaches a peak on the 1 st or 2 nd day 30 . The sera of rats with myocardial necrosis were worthy of particular attention because of the possibility that destruction of cardiac muscle, rich in transaminase activity, results in a release of this enzyme into blood stream and thus increase the serum transaminase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid peroxidation and anti-oxidant change and their significance during myocardial injury have provided a new insight in the pathogenesis of heart disease (Yogeeta et al, 2006). The increased level of free radical generating system and malondialdehyde (MDA) and lowered levels of free radical scavenging systems seem to have critical role in ischemic heart condition (Pandry et al, 2000).…”
Section: Introductionmentioning
confidence: 99%